Future and importance of cotton in West Africa : Malian case - (:unkn) unknown (My University, 2013)
This thesis shows the interest of cotton in African economy particularly in Malian one founded about 70% on primary sector in that agricultural part is estimated between 60 and 70%. This last also employees 70% of working population. Following many perturbations ten years ago, on cotton world market, several questions appear concerning the future of this product. Therefore, in the first time, the historic analysis of statistic data with tables, graphics, pictures prove the cotton importance in Mali, Africa and the world in multiple dimensions (economic, social , cultural and in environment). In this situation, appear many conflicts which conduct to a called phenomenon “cotton war “. Many historic and geopolitics reasons, explain this cotton world war which main characteristics are no limit discussions and negotiations at the World Trade Organization which is unable to oblige members to respect its main rules that are to forbid tariffs and trade barriers and others specially by “price makers “ countries. Another characteristic of cotton war is the question of important American, European and Chinese subsidies paid by developed countries in favor of its producers in an error to disadvantage of poor countries producers singularly Africans. Several studies based on models and corporate assets certificate negative impacts between subsidies amount and world cotton price estimated by index A “cotlook”. This direct politics effect bears the world market of cotton about an average rate of 15% (between 3 to 28% by cases). In order to stop these subventions distortions, many agreements are founded about the cotton question, in first African Sector Initiative, a group of four cotton producer countries, since Cancun Ministry Conference in 2003, September, in the second position are UEMOA actions in favor it's cotton areas and the partnership European Union (EU)-Africa on cotton. Finally, in the third and last party of this thesis, cotton problem is high
Keywords: African Research